IDENTIFICATION OFF EMOTIVE WORDS IN COMPUTATIONAL LINGUISTICS AND THEIR TRANSLATION (Scientific journal of the Fergana State University, 2025)
The article discusses the main issues and methods of solving them in the field of computational linguistics and the identification of emotive words. Emotive words are lexical units that express feelings, emotions, and internal states, and their automatic analysis and translation pose significant challenges. The article analyzes methods for identifying emotive words, including lexical-semantic analysis, machine learning, and natural language processing (NLP) techniques. Additionally, the translation issues of emotive words and the importance of preserving context are highlighted.